Exploring the role of generative AI in supporting students with disabilities, through the lens of universal design for learning - Sakowicz, Marie; Hamidi, Foad (American Journal of STEM Education, 2025)
Special educators face challenges managing the time and resources needed to teach students with diverse needs. Creating individualized instructional materials that align with the needs and plans of each student is one of these challenges. In this qualitative study, we investigated how generative Artificial Intelligence (AI) tools can assist special educators in creating learning content tailored to the needs of students with disabilities within the framework of Universal Design for Learning (UDL). Understanding how special educators can utilize generative AI tools to create personalized learning content can inform future technology design and form the basis for developing professional development tools that support the effective use and adoption of these emerging technologies.